Avaliação da cor de bráquetes estéticos quando submetidos ao desafio corante - Flores, Felipe Wehner (2013)
This study aimed to determine the color stability of aesthetic brackets (plastic and ceramic) when stored in red wine, subjected to daily baths of wine, and immersed in distilled water for different periods. With the aid of a spectrophotometer (SP60 - XRite) and using the CIE L * a * b * system, the initial color parameters and after 15, 30, and 45 days were measured. Brackets of different composition and trademarks were evaluated: Composite (polycarbonate) and Ceramic (polycrystalline ceramic)from Dental Morelli, Maia (polycrystalline ceramic) and Zetta (monocrystalline ceramic)from Eurodonto Orthodontic Products. After the initial color measurements, brackets were divided into 12 groups (n = 10) according to storage media and trademark. The control group remained immersed in distilled water, the wine test group received daily baths of red wine for 15 minutes during the entire period of the study and the immersion test group remained immersed in red wine throughout the study. Repeated readings were performed at 15, 30,and 45 days. Data were submitted to ANOVA and Tukey s test (5%). Color changes were observed in all tested materials, with the greatest change found in group immersioned in red wine, followed by the group subjected to daily baths, and the group stored in distilled water. The polycarbonate showed the greatest color change comparing to ceramics, and the polycrystalline ceramic demonstrated greater color change than monocrystalline ceramic. For all tested groups, the longer the period the greater the changes in color. The type of material and the time in contact with the staining agente had a directly influence in the color stability of brackets.